Determining the Performance of Maqhasid of General Islamic Banks in Indonesia - SETIYANINGSIH , Titik Agus; HARTINAH , Siti; HANUN, Nur Ravita (Journal of Governance, Taxation and Auditing, 2025)
This study aims to discuss the determinants of Maqashid Syariah performance using ROA, NPF, CAR, and ICG as independent variables. This study uses an associative quantitative approach. The data used are secondary data, namely, financial report data from Islamic Commercial Banks from 2019 to 2023. The population used in this study is BUS in Indonesia registered with the Financial Services Authority (OJK) during the 2019-2023 period. The sampling technique used was a purposive sampling method. The data obtained are annual reports of 7 Islamic commercial banks and 35 data for 5 consecutive years. The results of the study state that ROA has no significant effect on Maqashid Syariah performance, NPF has a significant negative effect on Maqashid Syariah performance, and CAR and ROA have a significant positive effect on Maqashid Syariah performance in Islamic commercial banks in Indonesia. Based on the research results, there are several implications, namely: (1) Islamic Commercial Banks must improve their financing schemes with profit-sharing patterns that are most in accordance with Sharia, do not use profit-sharing patterns that are similar to usury or other terms, and margin. This refers to the significant results of the performance of Islamic Commercial Banks in relation to upholding justice; (2) The performance of maqhasid sharia is influenced by ICG. Therefore, Islamic Commercial Banks need to improve Islamic governance as a form of capital and spiritual accountability to society and Allah SWT to develop business in an Islamic manner.